ANALISIS FAKTOR-FAKTOR INTERNAL DAN EKSTERNAL YANG MENINGKATKAN IBU HAMIL MENGANDUNG ANAK DOWN SYNDROM - Kusmantioko, Lisnur Isnaeni; Safitri, Ni’mah Alawiyah; Khasanah, Ivolia Indah Uswatun (Pattimura University, 2024)
This study aims to determine the internal factors and external factors that cause children to experience Down syndrome. The method used is a qualitative approach with a case study that interviewed three samples of Down syndrome sufferers in Semarang City. The results showed that the interviewed Down syndrome sufferers did not have a hereditary or family history of Down syndrome. However, the age of the mother when she was pregnant with a child with Down syndrome was ≥33 years, where the age of the mother greatly affects the maturity of the female reproductive organs. This study concludes that the factors that cause children to have Down syndrome include, among others, internal factors in the form of nondisjunction on chromosome 21. A fetus that should produce two copies of chromosome 21 instead produces three copies of chromosome 21, resulting in a baby who usually only has 46 chromosomes having 47 chromosomes. External influencing factors include maternal age, genetics, radiation, and nutrition (folic acid). Of the three subjects, the most dominant factor is the mother's age.